Keywords : a Vocabulary of Culture and Society. - Williams, Raymond (Oxford University Press, USA, 1985)
Now revised to include new words and updated essays, Keywords focuses on the sociology of language, demonstrating how the key words we use to understand our society take on new meanings and how these changes reflect the political bent and values of society.